The relationship between sport-specific training and a perceptuo-motor skills assessment as part of talent identification in young table tennis players (8-10 years) - Faber, I.; Zamoscinska, M.; Teunissen, J. W.; Pion, J. (International Journal of Racket Sports Science, 2020)
A perceptuo-motor skills assessment was developed to better estimate the potential of youth table tennis players (8-10 years). Sport-specific training experience might influence the outcomes of this assessment and hinder a fair interpretation. Consequently, the aim of this study was to evaluate the relationship between the training experience (i.e. quantity and quality) and the perceptuo-motor skills assessment outcomes in youth table tennis players. For this purpose, data were collected during the national association`s talent days in the Netherlands (2010-2015). In total, 372 young table tennis players (8-10 years) were assessed by a perceptuo-motor skills questionnaire covering current training (hours/week), total training volume (hours) and quality of the trainer (high versus low). Non-parametric partial correlation analyses showed that training quantity outcomes (i.e. current training and training volume) are significantly associated with the test items of speed while dribbling, aiming at target and eye-hand coordination in both sexes with small to medium effect sizes. The multivariate GLM analyses revealed no significant differences between players receiving high versus low quality training regarding the perceptuo-motor skills assessment. The results indicated only a small transfer of skill and a substantial amount of task specificity; as such it seems legitimate to use the perceptuo-motor skills assessment as part of a talent identification programme. However, it seems sensible to take the training volume into account for a fair interpretation of the estimation of potential, especially when large differences exist between players regarding the training experience. Future studies using a longitudinal design could reveal more about the effect of training.